2020
DOI: 10.3389/fpsyg.2020.01175
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Abusive Supervision and Abusive Supervision Climate on Employee Creativity: A Moderated Mediation Model

Abstract: In accordance with social identity theory, a multi-level model is put forward to investigate how the "conjoint" associations between abusive supervision and abusive supervision climate exert influence on employee creativity through creative role identity. The data in this paper were from 357 supervisor-subordinate dyads in 77 working groups to test the proposed model. The results indicated that creative role identities mediated the relationship between abusive supervision and employee creativity, and group-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…In addition to conservation of resource theory, some studies have used social exchange theory (Bandura, 1977 , 1978 ; Shen et al, 2020b ), psychological safety theory and social identification theory (Liu et al, 2016b ; Zhu and Zhang, 2019 ) to study the relationship between abusive supervision and creativity. However, we know that creativity is an activity outside the scope of work that requires an individual to invest many resources.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to conservation of resource theory, some studies have used social exchange theory (Bandura, 1977 , 1978 ; Shen et al, 2020b ), psychological safety theory and social identification theory (Liu et al, 2016b ; Zhu and Zhang, 2019 ) to study the relationship between abusive supervision and creativity. However, we know that creativity is an activity outside the scope of work that requires an individual to invest many resources.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This abusive supervision would affect employees' ability to access resources which in turn will affect employees' creativity. Although some studies have shown that abusive supervision can affect employees' creativity (Liu et al, 2016b ; Shen et al, 2020a , b ), the specific impact mechanism needs to be explored further due to the complex relationship between leadership and employee creativity. Therefore, it is necessary to investigate the impact mechanism of abusive supervision on creativity to improve employees' creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's competitive and rapidly changing business environment, scholars are increasingly interested in understanding how to enhance creativity in organizations (Shalley et al, 2004(Shalley et al, , 2009. One vein of research attempts to describe the relationship between abusive supervision and creativity (Liu et al, 2012;Lee et al, 2013;Shen et al, in press), and focuses on the impact of abusive supervision on creativity at the individual employee level (Liu et al, 2012(Liu et al, , 2016Zhang et al, 2014;Gu et al, 2016;Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An abusive supervision climate comprises the ideas employees have about abusive supervision in their department (Priesemuth, Schminke, Ambrose, & Folger, 2014). Studies have indicated that abusive supervisor climate contributes to negative outcomes, like negative associations with creative role identity (Shen, Yang, & Hu, 2020) at the individual-level and group performance and group citizenship behaviours at the department-level (Priesemuth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%